P E R B E D A A N P E N I N G K A T A N T E K A N A N D A R A H PADA PENGGUNAAN KONTRASEPSI SUNTIK 1 BULAN DAN 3 BULAN PADA AKSEPTOR ALAT KONTRASEPSI SUNTIK DI DESA JATIMULYO KECAMATAN MANTINGAN KABUPATEN NGAWI - Warsini Warsini; Herlina Puri Rahayu (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
The study was conducted because of differences in the content of the injectablecontraceptive 1 and 3 months, but they both can increase blood pressure.Purpose of the study was to determine differences in blood pressure increase in the useof injectable contraceptive 1 and 3 months.The subjects who used was the acceptor injectable contraceptive in Jatimulyo with a large32 samples were taken randomly. This research method was comparative analyticalresearch with crossectional design. Data were analyzed by independent t-test, p = 0.005using SPSS for windows 18 series.The results on this study was the average of systolic on the use of contraceptive 1 monthhas been increased from 121.25 mmHg to 140.63 mmHg, whereas the average ofdiastolic has been increased from 78.13 mmHg to 86.88 mmHg. The average of systolicon the use of contraceptive 3 months has been increased from 111.88 to 130 mm Hg,whereas the average of diastolic has been increased from 71.88 mmHg to 83.13 mmHg.It can be concluded that there was no significant difference between the increase insystolic blood pressure (95% CI 2.63 to 18 637; p = 0.11) or diastolic (95% CI 2273 to9773; p = 0.213) on the use of both injectable contraceptive 1 month and 3 months.Keywords: injectable contraceptives, blood pressure